2004
DOI: 10.1016/j.envres.2003.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral evaluation for a community with chronic exposure to hydrogen sulfide gas

Abstract: In May 2000, the Agency for Toxic Substances and Disease Registry of the US government conducted a health investigation in response to community concerns regarding ambient and indoor hydrogen sulfide (H 2 S), odor, and health symptoms in Dakota City, Nebraska. The objective was to determine whether adult residents in an area with repeated exposure to H 2 S showed poorer performance on neurobehavioral tests than unexposed residents. Study participants were required to meet age (X16 years of age) and length of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
0
15
1
1
Order By: Relevance
“…Spot measurements we have taken show that H 2 S concentrations greater than 1,000 ppb sometimes occur in some areas. Possibly the most comparable other study is by Inserra et al (2004), who administered a neuropsychological test battery to residents of two Nebraska cities with H 2 S exposures, occasionally in excess of 1000 ppb. The study area was divided into an “exposed” area, which sometimes experienced H 2 S concentrations ≥ 90 ppb (171 participants), and a comparison area with < 50 ppb exposures (164 participants).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spot measurements we have taken show that H 2 S concentrations greater than 1,000 ppb sometimes occur in some areas. Possibly the most comparable other study is by Inserra et al (2004), who administered a neuropsychological test battery to residents of two Nebraska cities with H 2 S exposures, occasionally in excess of 1000 ppb. The study area was divided into an “exposed” area, which sometimes experienced H 2 S concentrations ≥ 90 ppb (171 participants), and a comparison area with < 50 ppb exposures (164 participants).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in a variety of cognitive outcomes, predominantly psychomotor speed, fine motor skills, memory, attention, and mood have been reported (Horton et al, 2009, Kilburn, 1993, 1997, 2003, Kilburn and Warshaw, 1995, Tvedt et al, 1991a, Tvedt et al, 1991b). In contrast, Inserra et al (2004) compared neuropsychological performance in persons with long-term H 2 S exposures above 130 μg/m 3 (94 ppb, ‘exposed’) to those with exposures below 70 μg/m 3 (51 ppb,‘unexposed’). The exposed group did the same as or better than the unexposed on 21 of 28 cognitive performance tests, but did worse on memory and grip strength.…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrated that exposure to H 2 S was associated with cognitive impairment [24]. However, in a community-based study on people with chronic exposure to H 2 S, the investigators revealed that deficits in overall neurobehavioral performance were not associated with such exposure [25].…”
Section: Discussionmentioning
confidence: 99%
“…1 Number of articles found in MEDLINE on the neurobehavioral effects from occupational, environmental and pharmaceutical exposure to neurotoxicants has recently been confirmed for low occupational exposure levels of styrene (Seeber et al 2004), toluene (Filley et al 2004), trichloroethylene (Reif et al 2003), and for low lead levels in children (Chiodo et al 2004). Neurobehavioral effects were also recently assessed for aluminum (Buchta et al 2003;He et al 2003), arsenic (Tchounwou et al 2004;Tsai et al 2003), carbon monoxide (Raub and Benignus 2002), dioxin (Lim et al 2004), ethylene dichloride (Bowler et al 2003b), hydrogen sulfide (Inserra et al 2004), manganese in children (Takser et al 2003), inorganic and organic mercury Grandjean et al 2003;Lucchini et al 2003), and polychlorinated biphenyls (Schantz et al 2003). Meta-analyses of neurobehavioral studies were published for lead and mercury exposure .…”
Section: Amount Of Published Literaturementioning
confidence: 95%